2005
DOI: 10.1161/circulationaha.105.540542
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Blockade Mediates Smooth Muscle Cell Apoptosis and Improves Survival in Rats With Pulmonary Hypertension

Abstract: Background-We previously reported that administration of elastase inhibitors reverses fatal pulmonary arterial hypertension (PAH) in rats by inducing smooth muscle cell (SMC) apoptosis. We showed in pulmonary artery (PA) organ culture that the mechanism by which elastase inhibitors induce SMC apoptosis involves repression of matrix metalloproteinase (MMP) activity and subsequent signaling through ␣ v ␤ 3 -integrins and epidermal growth factor receptors (EGFRs). This suggests that blockade of these downstream e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
146
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(156 citation statements)
references
References 45 publications
7
146
0
3
Order By: Relevance
“…MMP inhibition also did not improve epithelial repair and regeneration, suggesting that the epithelial lesion is likely primarily mediated by the alloimmune process. Interestingly, we found that administration of the MMP inhibitor during the developing phase of fibrosis (days [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], showed even better effects to reduce the airway obliteration. This result needs to be further confirmed and the underlying mechanism is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…MMP inhibition also did not improve epithelial repair and regeneration, suggesting that the epithelial lesion is likely primarily mediated by the alloimmune process. Interestingly, we found that administration of the MMP inhibitor during the developing phase of fibrosis (days [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], showed even better effects to reduce the airway obliteration. This result needs to be further confirmed and the underlying mechanism is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Normal BMPR2 signaling negatively regulates PDGF (52) and likely other growth-promoting factors implicated in the pathobiology of PAH, such as EGF (53). Since BMP4 induces differentiation of fetal lung fibroblasts into SMCs and inhibits their proliferation (54), lack of BMP4/BMPR2 interaction might expand the myofibroblast population of cells, accounting for the adventitial and intimal thickening of the PAs in PAH.…”
Section: Bmpr2 and Vascular Cell Dysfunctionmentioning
confidence: 99%
“…Epidermal growth factor (EGF) was found to be co localized with Tenascin C, an ECM component, in the vascular lesions in PAH patients [50]. EGFR signaling was further demonstrated to be deregulated in MCT induced PAH rats and treatment with EGF receptor inhibitor, PKI166, induced PASMC apoptosis and increased survival of the rats [51]. Increased levels of basic fibroblast growth factor (bFGF/FGF--2) have been found in plasma and urine samples from PAH patients [52].…”
Section: Other Growth Factorsmentioning
confidence: 99%
“…The current therapeutic approaches as well as above mentioned emerging strategies The muitikinase inhibitor, Sorafenib and the EGFR inhibitor, Iressa, have already shown to attenuate vascular remodeling in the animal models of PH [51,82] and appear promising for future therapy of PAH.…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%